2020
DOI: 10.1021/acs.jafc.9b06744
|View full text |Cite
|
Sign up to set email alerts
|

Difunctional Fluorescence Nanoparticles for Accurate Tracing of Nanopesticide Fate and Crop Protection Prepared by Flash Nanoprecipitation

Abstract: Facile fabrication of difunctional nanoparticles (NPs) for pesticide delivery and imaging is still a fascinating challenge. Here, water-dispersible difunctional NPs were developed using flash nanoprecipitation (FNP) where self-assembling amphiphilic block copolymers were used to encapsulate a highly hydrophobic model pesticide, Lambda-cyhalothrin, and the fluorescent dye Nile red. The particle size (ranging from 158 to 280 nm) and fluorescence property of NPs could be controlled by varying the flow rate or Nil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…incognita. Chen et al 122 prepared water-dispersed bifunctional fluorescent nanoparticles by rapid nanoprecipitation and used them to accurately track the distribution of pesticides on the surfaces of leaves in situ while avoiding interference from chlorophyll fluorescence. The bifunctional fluorescent nanoparticle suspension had high insecticidal activity and stability, which proved that rapid nanoprecipitation is feasible and has great potential for preparation of multifunctional fluorescent nanoparticles with the ability for in situ pesticide tracing and crop protection.…”
Section: Nanotechnology In the Preparation Of Controlled-release Form...mentioning
confidence: 99%
“…incognita. Chen et al 122 prepared water-dispersed bifunctional fluorescent nanoparticles by rapid nanoprecipitation and used them to accurately track the distribution of pesticides on the surfaces of leaves in situ while avoiding interference from chlorophyll fluorescence. The bifunctional fluorescent nanoparticle suspension had high insecticidal activity and stability, which proved that rapid nanoprecipitation is feasible and has great potential for preparation of multifunctional fluorescent nanoparticles with the ability for in situ pesticide tracing and crop protection.…”
Section: Nanotechnology In the Preparation Of Controlled-release Form...mentioning
confidence: 99%
“…The development, feasibility, and potential of the flash nanoprecipitation (FNP) method in the universal fabrication of multifunctional NPs with in situ pesticide tracing and crop protection capabilities was discussed by Chen and co-workers [ 32 ]. Among the numerous preparation strategies, FNP has several advantages, including a quick and continuous assembly process, efficient encapsulation rate, and controllable particle size [ 33 ].…”
Section: Improving Crop Production Via Nanotechnology-enabled Innovationsmentioning
confidence: 99%
“…Fluorescence measurements were used to reveal the internal aggregation state and rearrangement of molecules in the NPs. High-resolution IVIS imaging and confocal laser scanning microscopy analysis showed the deposition and distribution of NPs on leaves could be visualized while avoiding undesirable autofluorescence [ 32 ]. Similarly, the formulation of abamectin nanopesticide having extended photostability and sustained release was realized by using the continuous and scalable FNP technique.…”
Section: Improving Crop Production Via Nanotechnology-enabled Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Guo group prepared a lambda-cyhalothrin nanoformulation using the flash nanoprecipitation (FNP) method, which has good stability and high insecticidal activity. 18 Wang and colleagues prepared a polylactic acid-modified graphene oxide (PLA-GO) nanocarrier for the delivery of pyraclostrobin (Pyr). 19 They found that PLA-GO can improve the water solubility of Pyr and exhibits temperature-responsive controlled-release performance, which can effectively improve the control effect of Pry on plant diseases.…”
Section: Introductionmentioning
confidence: 99%